On Estimation of Number of Detectable Software Faults under Budget Constraint - Shinji Inoue (International Journal of Mathematical, Engineering and Management Sciences, 2017)
Checking software quality and reliability of developed software system is one of the important activities for developing highly-reliable software system. In software testing phase, which is located in the final stage of software development process, software faults remaining the developed software system must be eliminated as possible as the testing manager could. Further, it is also important to develop testing plan to conduct testing activities efficiently under the certain constraints because there are some constraints, such as cost and delivery, in the actual testing phase. This paper discusses method to estimate the number of detectable faults under constant budget constraint by applying a two-dimensional Weibull type software reliability model, in which the software reliability growth process depends on testing time and testing effort factors. We finally show numerical examples of our method by using actual data.